Prepubertal Use of Long-Term GnRH Agonists in Dogs: Current Knowledge and Recommendations - Sabine Schäfer-Somi; Duygu Kaya; Selim Aslan (Animals, 2022)
The search for an alternative approach of estrus control (induction or suppression) in dogs is an important issue and the use of slow GnRH agonist-releasing implants has been the subject of frequent research in recent years. Studies to date demonstrate that the short- and long-term effects of deslorelin implants applicated at different time points of the prepubertal period are similar to those of adult dogs; however, there are important differences. The age of the prepubertal bitch and the dosage appear to be the main determinants of the response to deslorelin, as well as the individual metabolism of the bitch. Recent studies reported that the deslorelin-mediated long-term delay of puberty does not have negative carry-over effects on subsequent ovarian functionality, serum steroid hormone concentrations, uterine health, and fertility; however, more molecular studies are needed to determine the effects of application time of GnRH agonists on hormone concentrations and peripheral receptor expression. Furthermore, the long-term effects of delay of puberty with deslorelin on joint health, tumor development, the immune system, and social behavior deserve further investigations.